2001
DOI: 10.1016/s0735-1097(01)01229-3
|View full text |Cite
|
Sign up to set email alerts
|

A remarkable medical story: benefits of angiotensin-converting enzyme inhibitors in cardiac patients

Abstract: The development of angiotensin-converting enzyme inhibitors (ACE inhibitors) has been one of the most remarkable stories in the treatment of cardiovascular diseases. Angiotensin converting enzyme inhibitors have several acute and sustained hemodynamic effects that are beneficial in the presence of left ventricular (LV) dysfunction. They increase cardiac output and stroke volume and reduce systemic vascular resistance as well as pulmonary capillary wedge pressure. The hemodynamic benefits are associated with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 81 publications
2
52
0
1
Order By: Relevance
“…217,218 As such, ACEIs are considered a cornerstone of treatment for HF with reduced EF in adults, with benefits in all New York Heart Association functional classifications.…”
Section: Aceis and Angiotensin Receptor Blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…217,218 As such, ACEIs are considered a cornerstone of treatment for HF with reduced EF in adults, with benefits in all New York Heart Association functional classifications.…”
Section: Aceis and Angiotensin Receptor Blockersmentioning
confidence: 99%
“…Of course, for any patient with NMD and dilated cardiomyopathy, ACEI or ARB treatment is recommended on the basis of clinical trials showing benefits in the absence of NMD. 217,218 Use of an ACEI carries risks of angioedema, chronic cough, and other side effects that are attributable to the mechanism of action of this category of medications. Selective pharmacological blockade of the angiotensin receptor was developed to bypass this mechanism of action while still achieving favorable neurohormonal antagonism.…”
Section: Aceis and Angiotensin Receptor Blockersmentioning
confidence: 99%
“…71,72 Several studies have shown that ACE inhibition reduces the incidence of HF and mortality after an acute MI, possibly by preventing LV remodeling, reinfarction, and sudden death. 73 In the SAVE trial, which enrolled patients with LVEF Ͻ40% and no symptoms and signs of HF, captopriltreated patients had a significantly reduced incidence of mortality and experienced a 22% reduction in the risk of hospitalization for HF and 25% of recurrent MI. 33 The Acute Infarction Ramipril Efficacy (AIRE) trial differed from SAVE in that the patients had overt signs of HF after an acute MI and a measure of LVEF was not obtained in all patients.…”
Section: Ace Inhibitorsmentioning
confidence: 99%
“…Angiotensin II has been shown to have a deleterious effect at different levels including the cardiac, vascular and renal tissues [4]. Pharmacological agents such as ACE inhibitors, that actively prevent the formation of angiotensin II, may therefore have favourable effects in terms of end-organ protewction, beyond their activity on blood pressure (BP) [5].…”
Section: Introductionmentioning
confidence: 99%